Beyond sentinel node algorithm. Toward a more tailored surgery for cervical cancer patients. (27th May 2016) - Fagotti, Anna; Pedone Anchora, Luigi; Conte, Carmine; Chiantera, Vito; Vizza, Enrico; Tortorella, Lucia; Surico, Daniela; De Iaco, Pierandrea; Corrado, Giacomo; Fanfani, Francesco; Gallotta, Valerio; Scambia, Giovanni
Abstract: Nowadays cervical cancer is frequently diagnosed at early stage. For these patients lymph node metastasis (LNM) is considered the most important prognostic factor. During the last decade many efforts have been made to reduce rate of complications associated with lymphadenectomy (LND). A great interest has arisen in sentinel lymph node (SLN) biopsy as a technique able to decrease number of LND performed and, at the same time, to assess lymph nodal status. High diagnostic performances have been reached thanks to SLN surgical algorithm. However, despite the efforts, about 25% of these patients undergo at least unilateral LND to meet NCCN recommendations. Data of women with International Federation of Gynecology and Obstetrics stage IA1‐IB1/IIA1 cervical carcinoma were retrospectively collected by six Italian institutions. All patients underwent complete preoperative staging workup and were primarily treated by radical hysterectomy and pelvic bilateral LND. A total of 368 patients with early‐stage cervical cancer were identified. Among them 333 (90.5%) showed no suspicious enlarged nodes at the preoperative magnetic resonance imaging (MRI). In this subset, tumor diameter ≥20 mm was the only independent predictor of LN status ( P  = 0.003). None of the 106 patients with negative MRI nodal assessment, with squamous and adenosquamous histotype and a tumor diameter less than 2 cm had LNM. Based on these results we propose a new modified SLN surgical algorithm that could safely reduce LND performed in patients with very low‐risk early‐stage cervical cancer. Abstract : There is a subgroup of patients at very low risk of lymph node metastasis. In these women, complete lymphadenectomy could be avoided without risk.